Burnout and its correlates − an empirical study conducted among education, higher education and health care professionals - Załuska, Urszula; Ślazyk-Sobol, Magdalena; Kwiatkowska-Ciotucha, Dorota (Wypalenie zawodowe i jego korelaty na podstawie badań empirycznych wśród pracowników edukacji, szkolnictwa wyższego oraz opieki medycznej, 2018)
Burnout has serious consequences both for individuals and the organizations they work in. The issue generates interest among psychologist and management professionals and – according to the subject literature – there is a growing demand for helping those professional groups who face the risk of experiencing the negative effects of an exhausting working life. The aim of this paper is to characterize the phenomenon of burnout in Poland in the selected professional groups. The primary research was conducted on June and July 2017 on the group of 153 people working in the following areas: healthcare, education, higher education. Two types of questionnaire were used for the purpose of this research. The first was an LBQ Burnout Questionnaire, which is an adaptation of an Italian Link Burnout Questionnaire. The other questionnaire was originally devised by the authors to assess the perception of the phenomenon among Polish employees. The article presents the results concerning all the methods used during research and compared the results of the LBQ and the original questionnaire
Econometrics = Ekonometria, 2018, Vol. 22, No. 1, s. 26-38
Keywords: burnout; statistical analysis; areas of healthcare; education and higher education; wypalenie zawodowe; analiza statystyczna; wyczerpanie emocjonalne; cynizm; obniżone poczucie osiągnięć osobistych; typ pracy a wypalenie; demograficzne korelaty wypalenia zawodowego